Penggunaan Media Adiktif (Animasi Media Interkatif) Untuk Pengenalan Huruf Abjad Pada Anak Usia Dini - Novitasari, Ulvi Nor; Yulianto, Dema; Iswantiningtyas, Veny (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
The purpose of this study is to create new innovations to develop learning media for children so as to make children motivated and attract children's interest in learning the introduction of letters of the alphabet. This ADDICTIVE media was created through the Power Point Application. ADDICTIVE media is equipped with a display of alphabet letters that vary in color, there are animated images to attract children's interest, and is equipped with voice messages if children are still confused about the letters of the alphabet. This ADDICTIVE media was created to introduce the letters of the alphabet to early children and introduce children to technology.This study uses a development research model with Borg and Gall theory as a reference.The process of stages in this research, the researcher simplifies and restricts into three stages, namely: data collection, product design and design validation. The results of the calculation of the validation assessment of the acquisition of a value of more than 0.50 means that the value of valid requirements and product feasibility is obtained, then the product made by the researcher can be categorized as valid (feasible) and the acquisition of a value of less than 0.50 can be categorized as invalid (not feasible). Suggestions for further research is that the results of this research can be used as research references and to be taken into consideration to further deepen further research that is more interesting for early childhood.